A Feature-Driven Requirements Engineering Approach for Software Product Lines - Oliveira, Raphael Pereira de; Insfran, Emilio; Abrahão, Silvia; Gonzalez-Huerta, Javier; Blanes, David; Cohen, Sholom; Almeida, Eduardo Santana de (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2013: Anais do VII Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2013)
The importance of Requirements Engineering within software development has long been established and recognized by researchers and practitioners. Within Software Product Lines (SPL), this activity is even more critical because it needs to cope with common, variable, and product-specific requirements not only for a single product but for the whole set of products in the family. In this paper, we present a Feature-Driven Requirements Engineering approach (FeDRE) that provides support to the requirements specification of software product lines. The approach follows a strategy where features are realized into functional requirements considering the variability captured in a feature model. It also provides guidelines on how to associate chunks of features from a feature model and to consider them as the context for the Use Case specification. The feasibility of the approach is illustrated in a case study for developing an SPL of mobile applications for emergency notifications. Preliminary evaluations on the perceived ease of use and perceived usefulness of requirements analysts using the approach are also presented.